2015
DOI: 10.1039/c5cp04947d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized ZnO/ZnO2 n–N straddling heterostructure achieved by oxygen plasma bombardment for highly selective methane sensing

Abstract: Metal oxide semiconductors have been extensively used as reducing gas sensors with major limitations regarding selectivity and operating temperature which is relatively high for most of the cases making the device unusable in some critical situations. Higher operating temperature is also associated with the higher power consumption, which goes against the miniaturization of the device. In order to resolve these problems, here we introduced a ZnO/ZnO2 straddling 'n-N' isotype heterostructure as a highly selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In this case, the band gap of n-type γ-Fe 2 O 3 ( E g = 2.1 eV) is smaller than that of n -ZnO ( E g = 3.2 eV). Again, the electron affinity of γ-Fe 2 O 3 (χ = 4.7 eV) is larger than that of ZnO (χ = 4.1 eV), which indicates that these two semiconductors can create an N–n straddling type heterojunction at the interface. , The energy band diagrams of ZnO/γ-Fe 2 O 3 N–n straddling heterojunction before and after exposure to different gases have been presented in the Scheme . The individual energy-band diagrams of ZnO and γ-Fe 2 O 3 are shown in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the band gap of n-type γ-Fe 2 O 3 ( E g = 2.1 eV) is smaller than that of n -ZnO ( E g = 3.2 eV). Again, the electron affinity of γ-Fe 2 O 3 (χ = 4.7 eV) is larger than that of ZnO (χ = 4.1 eV), which indicates that these two semiconductors can create an N–n straddling type heterojunction at the interface. , The energy band diagrams of ZnO/γ-Fe 2 O 3 N–n straddling heterojunction before and after exposure to different gases have been presented in the Scheme . The individual energy-band diagrams of ZnO and γ-Fe 2 O 3 are shown in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
“…12 There are also several reports on gas sensing by composite materials like ZnO−CuO, ZnO−In 2 O 3 , SnO 2 −CuO, and ZnO−ZnO 2 , to name a few. 14,15 Wang et al 16 have reported CuO nanoparticle decorated porous ZnO based H 2 S sensor, but the major drawback was long sensing and recovery time. Park et al 17 have fabricated H 2 S sensors based on In 2 O 3 -core/ ZnO-shell nanorods with an operating temperature of 300 °C and the device was tested at a very low concentration of 10− 100 ppm.…”
mentioning
confidence: 99%
“…In the composites, Zn 2+ ions can be substituted with Fe 3+ ions, decreasing the donor concentration and then the electrical conductivity [46] as for γ-Fe 2 O 3 (33%)/Al-ZnO NC. However, because ZnO and γ-Fe 2 O 3 are n-type semiconductor with different energy bands, when the loading of γ-Fe 2 O 3 is enough high, it can be assumed that a n-n straddling heterostructure is formed [47,48]. In this situation, due to the different work functions of the two phases, free electrons can easily migrate from γ-Fe 2 O 3 to the Al-ZnO because of the potential difference at the heterojunction interface [49], leading to the enhanced electrical conductivity as for γ-Fe 2 O 3 (56%, 83%)/Al-ZnO NCs.…”
Section: Electrical Behaviormentioning
confidence: 99%
“…12,13 In regards to ion implantation processes, such as plasma immersion ion implantation (PIII), these can produce changes both on the surface and in the internal structure, producing an amorphous oxide layer, due to the acceleration of ions into the metallic substrate. 11,[14][15][16] Finally, chemical treatments, for example electropolishing, allow for the removal of any surface contaminant and the passivation of the surface whilst obtaining a nano-smooth surface with a mirror like nish. 7,12,17 This study focuses on the surface preparation step of L605 alloys for their direct plasma amination.…”
Section: Introductionmentioning
confidence: 99%